Health-Promoting Models of Behavior of Foreign Children in Polish Schools: Research Study - Nazaruk, Stanisława; Sokołowska, Barbara; Dąbrowska, Izabela (Journal of Vasyl Stefanyk Precarpathian National University, 2024)
The article presents the results of the research concerning pedagogical observations of selected features characterizing the health-promoting models of behaviour in children and adolescents. The observations were conducted by teachers working in primary schools in Poland. The selection of the sample for the study was purposeful as it targeted foreign students attending primary schools in Poland in rural or urban areas. Altogether, the teachers carried out 211 pedagogical observations, which were then subjected to statistical analysis. Taking up the research topic in the assessment of health-promoting models of behaviour in children and adolescents is a current scientific issue due to the fact that the above-mentioned models of behaviour constitute the basis for the proper development of young people and determine the state of human health in childhood, as well as adulthood. On the other hand, conducting the research on a group of foreign children who came to Poland in recent years, mainly from Ukraine, will help diagnose their learned behaviours in times when they lack peaceful life. The research results will be helpful in school practice for Polish teachers in undertaking targeted educational activities and, if necessary, conducting interventions for those in need of support. Health-promoting models of behaviour are indicators of attitudes towards health, which result from the values adopted by individuals. Therefore, the need to advise, support and help young people to shape them properly should be emphasized.